Экспериментальное моделирование простатита у крыс на основе гипокинетического стресса - Лугин, И.А. (Таврический медико-биологический вестник, 2012)
В результаті експериментальних досліджень встановлено, що гіпокінетичний стрес різної тривалості на ультраструктурному рівні в клітинах ендотелію гемокапілярів передміхурової залози на 9 добу впливу у щурів всіх вікових груп призводить до проявів адаптивно-компенсаторних реакцій, а на 14 добу іммобілізації виникають прояви дисфункції ендотелію, виражені в інтрацелюлярному набряці, паранекрозі і некрозі ендотеліоцитів гемокапілярів. As a result of experimental researches were found , that the effect of hypokinetic stress during 9 days immobilization influence at rats of all age groups by formation of figures of adaptive-compensatory reactions in tissues and endothelium of prostate gland, but for 14 days action of hypo kinetic stress. It initiated of endothelium’s dysfunction, which expressed in intracellular edema, and phenomenon of paranecrosis and necrosis in endothelial cells of blood capillaries, and disintegration of connective tissue in stroma of prostate gland.